Mathematics carved in culture: an ethnomathematical analysis of the historic Raja Rokan Palace architecture - Cahayanik; Khikmi, Aqnial; Antasari, Dwi Ayu; Najmy, Zhafirah; Nurrahmawati (International Journal of Progressive Mathematics Education, 2023)
Purpose: This study explores the ethnomathematical constructs within the Istana Raja Rokan to bridge the gap between abstract geometry and indigenous Malay culture, addressing the lack of localized contexts in mathematics education.Design/methodology/approach: Using a qualitative-ethnographic design, the research conducted intensive fieldwork involving observation and semi-structured interviews with Datuk Adat (traditional elders) and cultural experts. The Istana Raja Rokan served as the primary artifact, analyzed through data reduction and triangulation. Findings: The study identified sophisticated mathematical applications, including trapezoidal prisms in foundations, linear proportions in jointless pillars, and axial symmetry in plant-based (pakis) and draconic carvings. These findings validate that Rokan Malay architecture embodies formal geometric principles, specifically in measuring and designing activities.Practical implications: The results provide a foundation for developing inquiry-based learning trajectories. By utilizing these architectural contexts, teachers can mitigate mathematics anxiety and enhance students' conceptual understanding through culturally relevant examples.Originality/value: This research offers a novel synthesis of architectural structural integrity and philosophical symbolism in Malay heritage, contributing a localized ethnomathematical framework to the national curriculum discourse.   Purpose: Penelitian ini mengeksplorasi konstruk etnomatematika pada Istana Raja Rokan untuk menjembatani kesenjangan antara geometri abstrak dan budaya lokal Melayu, guna mengatasi minimnya konteks lokal dalam pendidikan matematika. Design/methodology/approach: Menggunakan desain kualitatif-etnografi, penelitian melakukan kerja lapangan intensif melalui observasi dan wawancara semiterstruktur dengan Datuk Adat serta pakar budaya. Istana Raja Rokan menjadi artefak utama yang dianalisis melalui reduksi data dan triangulasi. Findings: Studi mengidentifikasi aplikasi matematis yang kompleks, meliputi prisma trapesium pada tapakan, proporsi linear pada tiang tanpa sambungan, serta simetri aksial pada ukiran pakis dan naga. Temuan memvalidasi bahwa arsitektur Melayu Rokan menerapkan prinsip geometri formal dalam aktivitas mengukur dan merancang. Practical implications: Hasil penelitian memberikan dasar pengembangan alur pembelajaran (learning trajectory) berbasis inkuiri. Melalui konteks arsitektur ini, guru dapat menurunkan kecemasan matematika dan meningkatkan pemahaman konseptual siswa melalui contoh budaya yang relevan. Originality/value: Penelitian ini menawarkan sintesis baru antara integritas struktural arsitektur dan simbolisme filosofis warisan Melayu, serta memberikan kontribusi kerangka etnomatematika lokal pada diskursus kurikulum nasional.